Looking for an argument? - Mack, Herb; Barlowe, Avram (New York: Inquiry in Teaching and Learning, 2002)
Contents: Course overview. Debate topics. Discussion format. Note - taking and critique. Articles. Essays. Essay critique.The evolution of looking for an argument?. Q and A. Student critiques
Include appendix
Keywords: Educación Superior